Prosthesis refusal and the ethics of care in J. M. Coetzee's Slow Man - Chiang, Michelle Hui Ling (2025)
In The Ethics of Care: Personal, Political, and Global, Virginia Held asserts that those in the position to care should exercise power in ways that avoid violence and damage, and that trust and mutuality should be fostered in place of benevolent domination. With reference to Held's idea of relational care, this essay close reads J. M. Coetzee's depiction of prosthesis refusal in Slow Man as a nuanced critique of caring actions that are devoid of relationality. At the center of the novel is the character Paul Rayment's refusal to get fitted with a prosthetic leg after a cycling accident. He reasons that it is dishonest to give others the false impression that he is not without a leg, even if the price he must pay for "honesty" includes giving up the chance to cycle again and the quality of life he had before the accident. But Coetzee is at pains to highlight that Rayment is a confused character, and behind the confused narrative of "honesty" lies a subtext of rebellion. Specifically, this is a rebellion against care without relationality. It provokes the question, in the absence of ill intention toward the care recipient could caring actions be perfectly benign? In this article, I read the refused prosthetic leg as more than a phantasmagorical symbol of the depicted healthcare professionals' seemingly empty appearance of care; it foregrounds relationality as the critically missing substance that could render caring actions unethical in the novel.